Sains dan Teknologi dalam Ketamaduan Islam: Analisa Epistemologi dan Metodologi - Moch Holil; Zainul Bakir Fauzi; Alfina Wildatul Fitriyah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Science and technology have developed along with human development in this universe. The history of human civilization requires efforts to manifest values ​​within the scope of their own perspective. The above facts can be proven with strong support for the purposes of science and technology itself, these are values ​​and include cultural views formed by humans themselves.